2016
DOI: 10.1038/nrcardio.2016.101
|View full text |Cite
|
Sign up to set email alerts
|

Precision medicine in cardiology

Abstract: The cardiovascular research and clinical communities are ideally positioned to address the epidemic of noncommunicable causes of death, as well as advance our understanding of human health and disease, through the development and implementation of precision medicine. New tools will be needed for describing the cardiovascular health status of individuals and populations, including 'omic' data, exposome and social determinants of health, the microbiome, behaviours and motivations, patient-generated data, and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
141
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 190 publications
(145 citation statements)
references
References 130 publications
0
141
0
4
Order By: Relevance
“…A final consideration is that pro-efferocytic therapies may provide an actionable opportunity for the oft-mentioned concept of precision cardiovascular medicine 83 . Genetic studies pursuing the heritable component of cardiovascular disease have shown that the majority of genome-wide significant loci confer risk for myocardial infarction independently of all classical risk pathways, suggesting a novel mechanism of action which is not being addressed by lipid lowering or antihypertensive therapies 38, 84, 85 .…”
Section: Opportunities For Translationmentioning
confidence: 99%
“…A final consideration is that pro-efferocytic therapies may provide an actionable opportunity for the oft-mentioned concept of precision cardiovascular medicine 83 . Genetic studies pursuing the heritable component of cardiovascular disease have shown that the majority of genome-wide significant loci confer risk for myocardial infarction independently of all classical risk pathways, suggesting a novel mechanism of action which is not being addressed by lipid lowering or antihypertensive therapies 38, 84, 85 .…”
Section: Opportunities For Translationmentioning
confidence: 99%
“…The introduction of new technologies such as high-resolution CT coronary imaging with fractional flow reserve, virtual reality, vascular robotic systems, and 3-D printing can be incorporated into personalized care to improve the efficacy as well as the safety of the treatment of patients with CVD [57] . Cardiologists can use their experience in personalized medicine to improve the efficiency of clinical research and provide more precise information to improve the health of individuals as well as populations [58] . In the future, artificial intelligence/ machine learning will likely assist physicians with differential diagnosis of the disease, suggest treatment options or recommendations, and provide cues for image interpretation to facilitate the practice of personalized medicine.…”
Section: Concluding Remarks and The Future Of Personalized Cardiologymentioning
confidence: 99%
“…10 Precision medicine ( Figure 1) implies targeting treatments to the needs of individual patients on the basis of genetic, phenotypic and psychosocial characteristics that distinguish a given patient from other patients with similar clinical presentations. 11 Inherent to this definition is the concept of integrating (in electronic health records) individual-level information (e.g.…”
Section: The Promise Of Precision Medicinementioning
confidence: 99%
“…Handling the information gathered: descriptive statistical associations will not necessarily advance (10), (11), (42), areas of research the information of how molecules interact mechanistically to produce diseases or lead to rational therapies. (78), (79), (80) N-of-1 trials: the inclusion of N-of-1 trial data into randomized controlled trial meta-analyses improves the precision of yielded treatment effects.…”
Section: Identifying Newmentioning
confidence: 99%